Photograph rallies: the social use of images in Colombia - Ramírez Rivillas, Laura Isabel (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This article analyzes three photographs taken within the framework of the social rallies presented in Colombia during 2021, in order to contribute to the reflection on the visual construction of social discontent in a country traversed by violence. The research undertakes a journey from the academic field of photography and the social sciences to wonder about the visual resources and the production conditions of these photographs that have in common protagonists who reported some place of vulnerability. The author investigates the viewsthat these images offer on the protests, and how they propose other forms of enunciation and visibility of the Colombian social crisis, and allow evocations of humanization and empathy.